How to deliver a great speech that will change minds and influence people : tips, tricks & expert advice for effective public speaking - Helweg, Richard, 1956- (Atlantic Publishing Group, Inc., 2015)
"Public speaking is an art, and some of the most effective communicators in history have been artists. Think of Steve Jobs, John F. Kennedy, Dale Carnegie, Martin Luther King, Jr., and even President Barack Obama -- all public figures known for their eloquence when delivering a speech. A perfectly delivered speech is something that takes time, practice, and knowledge. How to Deliver a Great Speech that Will Change Minds and Influence People: Tips, Tricks & Expert Advice for Effective Public Speaking is teeming with resources for public speaking, whether you are looking to get over your fear of speaking to a group of people or are running for political office and need an edge on your competition. According to The Phobia Clinic, fear of public speaking ranks among Americans' top dreads, surpassing fear of illness, flying, terrorism, and often the fear of death itself. It's no wonder delivering a speech can seem like a large hurdle for many people. Even the most brilliant ideas have to be communicated with poise and enthusiasm or the message will be lost due to poor delivery. You will discover how to overcome public speaking fright and phobia by being prepared, rehearsed, and ready for a number of unforeseen circumstances. You will learn how to write a memorable speech and how to impact and persuade your audience. This book also includes tips on understanding your audience, holding their attention, knowing what to talk about and what not to include, organizing your speech, perfecting your timing, handling Q&A sessions, and much more. You will also grasp how to put together informative, educational, and well-designed visual aides, including electronic presentations. How to Deliver a Great Speech that Will Change Minds and Influence People will also show you how you can gauge your audience's reaction and tailor the remainder of your presentation to have maximum appeal to the group you are speaking to. There's no need to worry with this book in your arsenal: You'll learn everything you need to know to deliver an expertly written speech with poise and confidence."--